Social Responsibility Indicators for Salinas' SMES and its impact on Human Development - Fraga-Rodríguez, Rafael (2015)
The paper reports a literature review on the concepts of corporate social responsibility (CSR) and interpretations of the concept of human development (HD), both drawn from various contributions to its current conceptual construction; for which consultations have been held at various national and international documents that included books, laws, acts and journal articles on digital media and paper, among others. The outcome of the review provided a selection of CSR indicators, built. by triangulation of approaches to determine the impact on the DH. The result allows determining indicators for studying the incidence of CSR. in the DH of the Canton Salinas CSR, Santa Elena province, in the period 2013-2014 (Conferencia de las Naciones Unidas sobre comercio y desarrollo, 2008).